Transcriptomics and physiological analyses unveil the distinct mechanisms of ATP and glucose-6-phosphate utilization in Phaeodactylum tricornutum - Zhang, Xiaohua; Cheng, Shuang; Gao, Zhengquan; Cui, Yulin; Yao, Qingshou; Qin, Jiayang; Liu, Xiangyong; Lin, Senjie (Frontiers in Marine Science, 2023)
Phosphoesters are a dominant component of marine dissolved organic phosphorus (DOP) and an important source of the phosphorus nutrient for phytoplankton, but the molecular mechanisms of their utilization by phytoplankton are divergent and poorly understood. In this study, we used the model diatom Phaeodactylum tricornutum to investigate and compare the utilization mechanisms of two different phosphoesters, adenosine triphosphate (ATP) and glucose-6-phosphate (G6P). We found that ATP and G6P can both be efficiently used to support the growth of P. tricornutum. Cells grown on ATP or G6P showed lower pigment contents and photosynthetic rates but higher cellular neutral lipids relative to those grown on NaH2PO4 (DIP). Surprisingly, in neither ATP nor G6P group were significant increases in whole-cell alkaline phosphatase (AP) activity detected, suggesting that utilization of both DOPs was not reliant on extracellular AP. Yet ATP-grown cultures released DIP into the medium (i.e. ATP hydrolyzed extracellularly) whereas G6P-grown cultures did not. Furthermore, transcriptomic and RT-qPCR results showed that the gene encoding 5’ nucleotidase (5NT) in the ATP group and PhoD in the G6P group were upregulated. These results indicated that different pathways are involved in the use of these two DOPs, with ATP being hydrolyzed extracellularly likely by 5NT (PHATRDRAFT_44177) to release DIP for uptake, and G6P being directly absorbed and hydrolyzed intracellularly likely by PhoD (PHATRDRAFT_45757). Nevertheless, P. tricornutum under ATP and G6P conditions showed more similar transcriptomic profiles to each other than either compared to DIP-grown cultures, indicating similar metabolic functions of these two DOPs. These findings demonstrate that despite the high similarity in transcriptomic response to ATP and G6P conditions, the utilization mechanisms of these phosphoesters in the same species can be totally different, and the lack of AP activity does not necessarily signal the absence of DIP deficiency or the absence of DOP utilization.